Comparison between universities in Indonesia and Malaysia: World-class college ranking perspectives - Tri Suyantiningsih; Askar Garad; Muhamad Sophian; Muhammad Agung Wibowo (Intelektual Pustaka Media Utama, 2023)
This study analyzes Indonesian and Malaysian universities in order to evaluate the reality of higher education in both countries, uncover the dynamics and causes influencing higher education, and disclose the similarities and contrasts between the Indonesian and Malaysian systems. Birdy's comparative descriptive method was used. This research relies on trustworthy global rating websites, statistics from the Indonesian and Malaysian Ministries of Higher Education, high-quality publications, and authoritative news. Indonesian higher education is largely entirely supported by the government and tuition fees at private universities. Due to a lack of collaboration between universities and industry groups, Indonesian higher education lacks a connection between scientific research, technical education, and the job market. Unlike Malaysia, it stresses scientific research, community service, and labor market demands. The researchers hypothesized the following processes based on the comparator countries: Adopting a productive university focused on output application via instruction and advice. Community-government and private-sector connections Using research to enhance firm products Collaboration with a firm or group to provide services that benefit them in exchange for participation in higher education goals, payment of expenditures, and use of outcomes. Through cooperative education, businesses and institutions may train and prepare university students for the job market.